Copper and cuproptosis: new therapeutic approaches for Alzheimer’s disease - Li, Xiao; Chen, Xinwang; Gao, Xiyan (Frontiers in Aging Neuroscience, 2023)
Copper (Cu) plays a crucial role as a trace element in various physiological processes in humans. Nonetheless, free copper ions accumulate in the brain over time, resulting in a range of pathological changes. Compelling evidence indicates that excessive free copper deposition contributes to cognitive decline in individuals with Alzheimer’s disease (AD). Free copper levels in the serum and brain of AD patients are notably elevated, leading to reduced antioxidant defenses and mitochondrial dysfunction. Moreover, free copper accumulation triggers a specific form of cell death, namely copper-dependent cell death (cuproptosis). This article aimed to review the correlation between copper dysregulation and the pathogenesis of AD, along with the primary pathways regulating copper homoeostasis and copper-induced death in AD. Additionally, the efficacy and safety of natural and synthetic agents, including copper chelators, lipid peroxidation inhibitors, and antioxidants, were examined. These treatments can restore copper equilibrium and prevent copper-induced cell death in AD cases. Another aim of this review was to highlight the significance of copper dysregulation and promote the development of pharmaceutical interventions to address it.